2023
DOI: 10.1002/jimd.12678
|View full text |Cite
|
Sign up to set email alerts
|

The challenge of understanding and predicting phenotypic diversity in urea cycle disorders

Roland Posset,
Matthias Zielonka,
Florian Gleich
et al.

Abstract: The Urea Cycle Disorders Consortium (UCDC) and the European registry and network for Intoxication type Metabolic Diseases (E‐IMD) are the worldwide largest databases for individuals with urea cycle disorders (UCDs) comprising longitudinal data from more than 1100 individuals with an overall long‐term follow‐up of approximately 25 years. However, heterogeneity of the clinical phenotype as well as different diagnostic and therapeutic strategies hamper our understanding on the predictors of phenotypic diversity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…The authors reap the benefits of the traditional use of ENS in Italy, which demonstrated that UCDs cannot be considered only in their acute forms and that late-onset cases can be detected in a relevant proportion of patients if suitable diagnostic processes are available. The relevance of ENS is confirmed by the recently published analysis of the two large databases gathered by the American and the European consortia [ 21 ]. Therefore, strategies to implement ENS with clinical observation and enzyme assessment to predict the patient’s evolution is of main importance [ 21 ].…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations
“…The authors reap the benefits of the traditional use of ENS in Italy, which demonstrated that UCDs cannot be considered only in their acute forms and that late-onset cases can be detected in a relevant proportion of patients if suitable diagnostic processes are available. The relevance of ENS is confirmed by the recently published analysis of the two large databases gathered by the American and the European consortia [ 21 ]. Therefore, strategies to implement ENS with clinical observation and enzyme assessment to predict the patient’s evolution is of main importance [ 21 ].…”
Section: Discussionmentioning
confidence: 73%
“…The relevance of ENS is confirmed by the recently published analysis of the two large databases gathered by the American and the European consortia [ 21 ]. Therefore, strategies to implement ENS with clinical observation and enzyme assessment to predict the patient’s evolution is of main importance [ 21 ].…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations